A speaking silence - Artaner, Cecilia; Verón, Natalia; Jorge, Soledad (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2021)
Interpretation as a speaking silence is not that which seeks to decipher, through the signifying articulation, the truth of the symptom. When the aim is the jouissance of the symptom, the interpretation is necessarily a different one. It must be a speaking silence, not the silence of impotence but that which breaks the signifying chain and introduces the hole that the unconscious covers with its own interpretation. It makes room for that which is veiled in the social bond. Psychoanalysis, as an unprecedented social bond at the level of culture, reminds us that there is something that can never enter into the bond with others, and that, far from rejecting it, it becomes the cause of new work in the social bond. In the age of virtuality, we ask ourselves, what social bond is possible without the body? How do these coordinates come into play in the analytical bond?